Direct Transformation of Amorphous Silicon Carbide into Graphene under Low Temperature and Ambient Pressure - Peng, Tao (Nature Publishing Group, 2013)
A large-scale availability of the graphene is critical to the successful application of graphene-based electronic devices. The growth of epitaxial graphene (EG) on insulating silicon carbide (SiC) surfaces has opened a new promising route for large-scale high-quality graphene production. However, two key obstacles to epitaxial growth are extremely high requirements for almost perfectly ordered crystal SiC and harsh process conditions. Here, we report that the amorphous SiC (a-Si(1−x)C(x)) nano-shell (nano-film) can be directly transformed into graphene by using chlorination method under very mild reaction conditions of relative low temperature (800°C) and the ambient pressure in chlorine (Cl(2)) atmosphere. Therefore, our finding, the direct transformation of a-Si(1−x)C(x) into graphene under much milder condition, will open a door to apply this new method to the large-scale production of graphene at low costs.